Synergetic Effect of Ru and NiO in the Electrocatalytic Decomposition of Li2CO3 to Enhance the Performance of a Li-CO2/O2 Battery - Zhang, Peng-Fang; Zhang, Jun-Yu; Sheng, Tian; Lu, Yan-Qiu; Yin, Zu-Wei; Li, Yu-Yang; Peng, Xin-Xing; Zhou, Yao; Li, Jun-Tao; Wu, Yi-Jin; Lin, Jin-Xia; Xu, Bin-Bin; et al. (ACS catalysis, 2020)
Li2CO3 is the cathodic discharge product of a Li-CO2/O2 battery and is difficult to electrochemically decompose. The accumulation of Li2CO3 leads to battery degradation and results in a short lifespan. Herein, a carbon nanotube supported Ru/NiO@Ni catalyst (Ru/NiO@Ni/CNT) is synthesized with Ru nanoparticles (∼2.5 nm) anchored on the surface of core–shell structure NiO@Ni nanoparticles (∼17 nm). We found strong interfacial interactions between Ru nanoparticles and NiO. XRD and XPS analysis revealed that the presence of Ru could protect the Ni species from being deeply oxidized while the NiO species could modify the local electronic structure of Ru, inducing a higher oxidation state. When such a Ru/NiO@Ni/CNT catalyst is used as a cathode in Li-CO2/O2 (v:v = 4:1) batteries, a long cycling life of 105 cycles at a cutoff capacity of 1000 mAh g–1 with an overpotential as low as 1.01 V was achieved, which is significantly better than 75 and 44 cycles with Ru/CNT and NiO@Ni/CNT catalysts, respectively, and confirms the strong synergetic effect between the Ru and NiO species in the electrocatalytic decomposition of Li2CO3. Density functional theory (DFT) calculations of the electrochemical decomposition of Li2CO3 with the assistance of RuO2 indicates that the formation of O2 is the rate-determining step. In addition, the formation and decomposition process of Li2CO3 was illuminated at a molecular level by in situ FTIR spectroscopy with Ru/NiO@Ni/CNT catalysts.